Sexuality and quality of life after nerve-sparing radical hysterectomy for cervical cancer: A prospective study - Marta Novackova; Zlatko Pastor; Roman Chmel, Jr.; Ivana Mala; Roman Chmel (Taiwanese Journal of Obstetrics & Gynecology, 2022)
Objective: Nerve-sparing radical hysterectomy (NSRH) decreases the negative postoperative consequences of radical surgery for cervical cancer, such as bladder evacuation disorders, colorectal motility disorders, and sexual dysfunction. The aim of this study was to prospectively assess the sexuality and quality of life in a group of women who underwent NSRH with lymphadenectomy for cervical cancer. Materials and methods: A total of 65 patients with early-stage cervical cancer underwent NSRH between 2014 and 2016. Patient examinations and questionnaire surveys (Female Sexual Function Index questionnaire and European Organization for Research and Treatment of Cancer questionnaires QLQ-C30 and QLQ-CX24) were conducted, before and one year after the surgery. Results: After the exclusion of 19 sexually inactive women and 10 women who received adjuvant anticancer treatment, 36 sexually active patients treated solely with nerve-sparing surgery were eligible for evaluation. The mean age was 47 years. The average preoperative vaginal length was 9.4 cm, whereas the postoperative length was shortened to 7.1 cm. This study showed no negative impact of NSRH on sexual desire, arousal, satisfaction, orgasm, pain, sexual activity, sexual enjoyment, and sexual worry. The worsening of sexual functioning was recorded during the one-year follow-up. The QLQ-C30 questionnaire confirmed postoperative improvement in global health status and role, emotional, and social functioning. Conclusion: Our study showed using standardized questionnaires that NSRH has no negative impact on sexual desire, arousal, satisfaction, orgasm, pain, sexual activity, frequency of sexual intercourse, sexual enjoyment, and sexual worry, while only the worsening of sexual functioning was recorded. Moreover, NSRH did not cause postoperative deterioration in the quality of life parameters.